Swamp thing : twin branches - Stiefvater, Maggie, 1981- (DC Comics, 2020)
"Twins Alec and Walker Holland have a reputation around town. One is quiet and the other is the life of any party, but the two are inseparable. For their last summer before college, Alec and Walker leave the city to live with their rural cousins, where they find that the swamp holds far darker depths than they could have imagined. While Walker carves their names into the new social scene, Alec recedes into a summer-school laboratory, slowly losing himself to a deep, dark experiment. This season, both brothers must confront truths, ancient and familial, and as their lives diverge, tensions increase and dormant memories claw to the surface"--